From habit to deep learning: teacher strategies for advancing elementary students’ reading literacy - Sri Dewi Nirmala; Ryan Dwi Puspita; Sendi Ramdhani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Reading literacy is a fundamental competency in elementary education and a prerequisite for lifelong learning. However, literacy skills in Indonesia, particularly reading literacy, indicate that students still face challenges with higher-order literacy skills, especially in making inferences, evaluating texts, and engaging in reflective reading. This situation highlights the importance of refining teachers' strategies, promoting meaningful reading habits, and using technology to support literacy through a deep-learning approach. This study aims to analyze (1) the level of reading literacy among elementary students, (2) the influence of reading habits and teacher instructional strategies on literacy development, and (3) teachers’ efforts to enhance literacy through learning models, technology, and deep learning-based experiences. The study employed a descriptive quantitative approach involving 124 elementary school teachers from 17 provinces in Indonesia. Data were collected using structured questionnaires and observation sheets, and subsequently analyzed using descriptive statistics. The results indicate varied literacy levels among students that (1) 15% require special intervention, (2) 40% are at the basic level, (3) 25% are at the proficient level, and (4) 20% are at the advanced level. Reading habit programs were implemented consistently and had a positive impact. However, they remained routine and insufficient in fostering reflective and critical thinking skills. Teachers played an active role in integrating literacy into learning, although the instructional strategies used to enhance literacy remained limited in variety and innovation. Technology integration appeared in implementation and assessment, but was mostly limited to the planning stage. A gap exists between teacher strategies and student literacy achievement. To bridge this gap, literacy instruction should shift from routine practices to a deep-learning-based approach grounded in the principles of meaningfulness, awareness, and enjoyment, accompanied by systematic teacher capacity building and technology integration to support sustainable literacy development.